Adverse Selection in Low-Income Health Insurance Markets: Evidence from an RCT in Pakistan - Fischer, Torben; Frölich, Markus; Landmann, Andreas (American Economic Journal: Applied Economics, 2023)
We present robust evidence on adverse selection in hospitalization insurance for low-income individuals that received first-time access to insurance. A large randomized control trial from Pakistan allows us to separate adverse selection from moral hazard, estimate how selection changes at different points of the demand curve, and test simple measures to limit adverse selection. The results reveal sub-stantial selection in individual policies, leading to welfare losses and the threat of a market breakdown. Bundling insurance policies at the household level or higher almost eliminates adverse selection, thus mitigating its welfare consequences and facilitating sustainable insurance supply. (JEL D82, G22, I13, I18, O15, O16)
CRIS-Team Scopus Importer:2023-07-28

Adverse Selection in Low-Income Health Insurance Markets: Evidence from an RCT in Pakistan - Fischer, Torben; Frölich, Markus; Landmann, Andreas (American Economic Journal: Applied Economics, 2023)
We present robust evidence on adverse selection in hospitalization insurance for low-income individuals that received first-time access to insurance. A large randomized control trial from Pakistan allows us to separate adverse selection from moral hazard, estimate how selection changes at different points of the demand curve, and test simple measures to limit adverse selection. The results reveal substantial selection in individual policies, leading to welfare losses and the threat of a market breakdown. Bundling insurance policies at the household level or higher almost eliminates adverse selection, thus mitigating its welfare consequences and facilitating sustainable insurance supply. <br

Building trust in rural producer organizations: Results from a randomized controlled trial - Bernard, Tanguy; Dänzer, Pia Naima; Frölich, Markus; Landmann, Andreas; Viceisza, Angelino; Wouterse, Fleur (Agricultural and Resource Economics Review, 2021)
Trust is considered an important factor for successful collective action in groups of smallholder farmers. A prime example is collective commercialization of agricultural produce through producer organizations. While previous research has focused on trust as an exogenous determinant of participation in groups, this article tests whether trust within existing groups can be improved using a training program. We conduct a cluster-randomized controlled trial in rural Senegal to identify the effects of training members and/or leaders with respect to commercialization on intragroup trust. Our design allows identifying both direct treatment effects of having participated in the training and spillover effects on farmers who did not partake. Looking at different measures of trust in leaders' competence and motives and of trust in members, we find that participating in the training significantly enhances both trust in leaders and trust in members. For trust in leaders, we also find a strong spillover effect. Our findings suggest that relatively soft and noncostly interventions such as group training appear to positively affect trust within producer organizations.
CRIS-Team Scopus Importer:2021-09-24
Keywords: rural producer organizations; Senegal; trust

Can group incentives alleviate moral hazard? The role of pro-social preferences - Biener, Christian; Eling, Martin; Landmann, Andreas; Pradhan, Shailee (European Economic Review, 2018)
Incentivizing unobservable effort in risky environments, such as in insurance, credit, and labor markets, is vital as moral hazard may otherwise cause significant welfare losses including the outright failure of markets. Ensuring incentive-compatibility through state-contingent contracts between principal and agent, however, is undesirable for risk-averse agents. We provide a theoretical intuition on how pro-social preferences between agents in a joint liability group contract can ensure incentive-compatibility. Two independent large-scale behavioral experiments framed in an insurance context support the hypotheses derived from our theory. In particular, effort decreases when making agents' payoff less state-dependent, but this effect is mitigated with joint liability in a group scheme where agents are additionally motivated by pro-social concerns. Activating strategic motives slightly increases effort further; particularly in non-anonymous groups with high network strength. The results support existing evidence on joint liability groups and further suggest that even if peer pressure to ensure effort provision is absent, such group policies can improve efficiency when agents are pro-social.
Created from Fastlane, Scopus look-up
Keywords: Experiment; Group joint liability; Moral hazard; Pro-social preferences

Can health-insurance help prevent child labor? An impact evaluation from Pakistan - Landmann, Andreas; Froelich, Markus (Journal of Health Economics, 2015)
Child labor is a common consequence of economic shocks in developing countries. We show that reducing vulnerability can affect child labor outcomes. We exploit the extension of a health and accident insurance scheme by a Pakistani microfinance institution that was set up as a randomized controlled trial and accompanied by household panel surveys. Together with increased coverage the microfinance institution offered assistance with claim procedures in treatment branches. We find lower incidence of child labor, hazardous occupations and child labor earnings caused by the innovation. Boys are more often engaged in child labor in our sample, but also seem to profit more from the insurance innovation.
Created from Fastlane, Scopus look-up
Keywords: Child labor; Health insurance; Microinsurance; Pakistan; Vulnerability

Contract nonperformance risk and uncertainty in insurance markets - Biener, Christian; Landmann, Andreas; Santana, Maria Isabel (Journal of Public Economics, 2019)
Insurance contracts may fail to perform, leading to a default on valid claims. We relax the standard assumption of known probabilities for such defaults by allowing for uncertainty. Within a large behavioral experiment, we show that introducing risk and uncertainty each leads to significant reductions in insurance demand and that the effects are comparable in magnitude (17.1 and 14.5 percentage points). Furthermore, risk- and ambiguity-averse participants are affected most. These findings are in line with models incorporating ambiguity attitudes or, alternatively, pessimistic beliefs. An analysis of the belief and decision dynamics suggests persistent pessimistic priors and disregard of peer experiences, leading to a stable uncertainty effect.
Created from Fastlane, Scopus look-up
Keywords: Ambiguity preferences; Contract nonperformance; Insurance; Pessimistic beliefs; Uncertainty

Cooperation and authoritarian values: An experimental study in China - Vollan, Bjorn; Landmann, Andreas; Zhou, Yexin; Hu, Biliang; Herrmann-Pillath, Carsten (European Economic Review, 2017)
Using samples of both students and workers in China and comparing democratic decision making (i.e. being able to choose one's rules) to non-democratic decision making (i.e. exogenously imposed rule), we show that Chinese participants cooperate the most in a public goods game under the stylized authoritarian environment. This finding may be surprising in light of previous evidence for a “democracy premium” but is in line with authoritarian norms which are prominent in China. We further show that there is a systematic association between participants’ values and their relative contribution decisions in exogenous and endogenous implementation of the rule. Our major finding is that those subjects that place greater value on accepting authority are responsible for greater levels of cooperation under top-down governance. Our findings provide evidence that the effectiveness of a political institution depends on its congruence with individual values and societal norms.
Created from Fastlane, Scopus look-up
Keywords: Authoritarian values; China; Democratic voting; Legitimacy of legal sanctions; Public goods

Does free hospitalization insurance change health care consumption of the poor? Short-term evidence from Pakistan - Helmsmueller, Simona; Landmann, Andreas (Geneva Risk and Insurance Review, 2021)
We analyze short-term effects of free hospitalization insurance for the poorest quintile of the population in the province of Khyber Pakhtunkhwa, Pakistan. First, we exploit that eligibility is based on an exogenous poverty score threshold and apply a regression discontinuity design. Second, we exploit imperfect rollout and compare insured and uninsured households using propensity score matching. With both methods we fail to detect significant effects on the incidence of hospitalization. Whereas the program did not meaningfully increase the quantity of health care consumed, insured households more often choose private hospitals, indicating a shift towards higher perceived quality of care.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Health care consumption; Health insurance; Pakistan; Program evaluation; Universal health care

Effects of Insurance on Child Labour: Ex-Ante and Ex-Post Behavioural Changes - Froelich, Markus; Landmann, Andreas (Journal of Development Studies, 2018)
In this paper we analyse possible effects of insurance on child labour. First, we develop a theoretical model that separates effects of insurance with and without a shock taking place. We then empirically test the hypotheses derived from the model by analysing the extension of a health insurance product in urban Hyderabad in Pakistan. Consistent with the theoretical model we develop in this paper, the reduction in child labour caused by the extension is largely due to an ex-ante feeling of protection as opposed to an ex-post shock-mitigation effect.
Created from Fastlane, Scopus look-up

Gender preferences in the CEO successions of family firms: Family characteristics and human capital of the successor - Ahrens, Jan-Philipp; Landmann, Andreas; Woywode, Michael (Journal of Family Business Strategy, 2015)
Reviews of the literature reveal that empirical work on gender and CEO successions in family firms is still rare. Building on a unique data set of CEO successions, we investigate labor market constraints in CEO succession contests in family firms with concentrated ownership. We find that a preference for male family heirs limits labor market selectivity. Furthermore, we find that only 23% of all single family successors in our sample are females, indicating that males are still the preferred choice. Family successions are significantly more likely to occur when the predecessor has a son. Under specific family structures, such as when both genders are represented among the predecessors' children, the number of female successors decreases to 19% of family successions with one successor. Sons increase the likelihood of CEO succession contest constraints. We observe that the selected female family successors seem to be equipped with higher levels of human capital compared to the selected male family successors. Our results indicate that male family successors are chosen not because of higher human capital levels but because of the contest rulers' gender preferences in favor male family heirs, which adversely affect the selectivity of CEO succession contests.
Created from Fastlane, Scopus look-up
Keywords: CEO succession; Family characteristics; Family firms; Human capital; Male and female business leaders; Promotion decisions

Patrilocal Residence and Female Labor Supply: Evidence From Kyrgyzstan - Landmann, Andreas; Seitz, Helke; Steiner, Susan (Demography, 2018)
Many people live in patrilocal societies, which prescribe that women move in with their husbands’ parents, relieve their in-laws from housework, and care for them in old age. This arrangement is likely to have labor market consequences, in particular for women. We study the effect of coresidence on female labor supply in Kyrgyzstan, a strongly patrilocal setting. We account for the endogeneity of coresidence by exploiting the tradition that youngest sons usually live with their parents. In both OLS and IV estimations, the effect of coresidence on female labor supply is negative and insignificant. This finding is in contrast to previous studies, which found positive effects in less patrilocal settings. We go beyond earlier work by investigating effect channels. In Kyrgyzstan, coresiding women invest more time in elder care than women who do not coreside, and they do not receive parental support in housework.
Created from Fastlane, Scopus look-up
Keywords: Coresidence; Family structure; Kyrgyzstan; Labor supply; Patrilocality

Pro-sociality of local democratic leaders: The impact and dynamics of being elected - Landmann, Andreas; Vollan, Björn (European Economic Review, 2024)
Democratic regimes need leaders with high intrinsic motivation to serve their constituents. In this paper, we investigate the levels of leaders’ pro-social motivation, how such levels differ from those of villagers, whether they are affected when the leaders are elected, and the persistence over several years. A regression discontinuity design based on close elections combined with a panel of incentivized lab-in-the-field measures of solidarity reveals that being elected and holding office as a local leader results in making more pro-social choices two and six years after the election. An additional experiment measuring normative expectations towards leaders suggests that leaders' higher pro-sociality may come from internalizing these expectations. We also discuss the role of income, collective action and network ties and how the increase in pro-sociality relates to local level corruption.
CRIS-Team Scopus Importer:2024-04-05
Keywords: C90; D90; Democratic leadership; Injunctive norms; Lab-in-the-field; O12; Philippines jel: D72; Pro-sociality; Political selection

Recovery mode: Non-cognitive skills after the storm - Biener, Christian; Landmann, Andreas (World Development, 2023)
We analyze the very short-term causal impact of exposure to one of the most powerful storms ever recorded to strike land on locus of control, beliefs in reciprocity, and risk preferences within a sample of 2,352 individuals. We find that people exhibit significantly lower external locus of control, beliefs in reciprocity, and risk aversion after the shock. Our identification is based on field work that coincidentally started shortly before the typhoon and that continued thereafter. The short-term impact we document has not been observed previously, and we thus fill a gap in the emerging literature on the stability of non-cognitive skills. (c) 2022 The Author(s). Published by Elsevier Ltd. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/).
CRIS-Team WoS Importer:2023-01-13

Self-governance and punishment: An experimental study among namibian forest users - Vollan, Bjoern; Proepper, Michael; Landmann, Andreas; Balafoutas, Loukas (Economic Development and Cultural Change, 2019)
We use a framed field experiment to assess resource harvesting behavior and its interaction with prosocial and antisocial punishment in the Kavango woodland savannah of Namibia. We implement two treatments, one with external, centralized punishment and one with internal, decentralized punishment. Our findings suggest that institution type matters, as internal punishment is a more effective regime to discipline high harvesters compared with external punishment. We find that antisocial punishment (i.e., the sanctioning of people who cooperate by free riders) happens frequently, partly as revenge and especially in ethnically heterogeneous groups, but ultimately does not prevent cooperative self-governance.
Created from Fastlane, Scopus look-up

Unmasking the myth of the same-sex teacher advantage - Neugebauer, Martin; Helbig, Marcel; Landmann, Andreas (European Sociological Review, 2011)
Trend statistics reveal a striking reversal of a gender gap that has once favoured males: girls have surpassed boys in many aspects of the educational system. At the same time, the share of female teachers has grown in almost all countries of the western world. There is an ongoing, contentious debate on whether the gender of the teacher can account, in part, for the growing educational disadvantage of males. In this study, we use large-scale data from IGLU-E, an expansion of PIRLS in Germany, to estimate whether there is a causal effect of having a same-sex teacher on student outcomes. We estimate effects for typical 'female' subjects and typical 'male' subjects as well as for different student outcomes (objective test scores and more subjective teacher's grades). We find virtually no evidence of a benefit from having a same-sex teacher, neither for boys nor for girls. These findings suggest that the popular call for more male teachers in primary schools is not the key to tackling the growing disadvantage of boys. © 2010 The Author Published by Oxford University Press. All rights reserved.
Created from Fastlane, Scopus look-up

Un/met: a mixed-methods study on primary healthcare needs of the poorest population in Khyber Pakhtunkhwa province, Pakistan - Shaukat, Maira; Imping, Alina; Rogge, Lisa; Khalid, Fatima; Ullah, Safat; Ahmad, Fayaz; Kibria, Zeeshan; Landmann, Andreas; Khan, Zohaib; De Allegri, Manuela (International Journal For Equity in Health, 2024)
Background: Access of all people to the healthcare they need, without financial hardship is the goal of Universal Health Coverage (UHC). As UHC initiatives expand, assessing the needs of vulnerable populations can reveal gaps in the system which may be covered by relevant policies. In this study we (i) identify the met and unmet primary healthcare needs of the poorest population of Khyber Pakhtunkhwa province (KP), Pakistan, and (ii) explore why the gaps exist. Methods: We used Leveque’s Framework of Patient-centred Access to Healthcare to examine unmet primary healthcare (PHC) needs and their underlying causes for the poorest population in four districts of Khyber Pakhtunkhwa province, Pakistan. Using a triangulation mixed methods design, we analysed data from a quantitative household survey of744 households, 17 focus group discussions with household members and, 11 interviews with healthcare providers. Results: Our results show that indicate that despite service utilization, PHC needs were not met, primarily due to prohibitively high costs at each stage of access. Furthermore, gaps in outreach and information (approachability), and varying availability of medicines and diagnostics at facilities (appropriateness) the supply side as well as difficulties in navigating the system (inability to perceive) and adhering to prescriptions (inability to engage) on the demand side, also led to unmet PHC needs. Going beyond utilization, our findings highlight that engagement with care is an important determinant of met needs for vulnerable populations. Conclusion: Social health protection policies can contribute to advancing UHC for primary care. However, in our setting, enhancing communication and outreach, addressing gender and age disparities, and improving quality of care and health infrastructure are necessary to fully meet the needs of the poorest populations.
CRIS-Team Scopus Importer:2024-10-04
Keywords: Access to primary care; Health equity; Needs assessment pakistan; Primary health care; Universal health coverage; Universal health insurance